2012
DOI: 10.1186/1756-0500-5-61
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of scientific thinking in basic science in the Iranian second national Olympiad

Abstract: BackgroundTo evaluate the scientific reasoning in basic science among undergraduate medical students, we established the National Medical Science Olympiad in Iran. In this Olympiad, the drawing of a concept map was used to evaluate a student's knowledge framework; students' ability in hypothesis generation and testing were also evaluated in four different steps. All medical students were invited to participate in this program. Finally, 133 undergraduate medical students with average grades ≥ 16/20 from 45 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Science learning is oriented to the development of caring and responsible attitude towards the social and natural environment (Kabba, 2009;Hewitt et al, 2013). In learning, the material acts as the relationship among separated data sources (Morrison et al, 2007;Adam & Carl, 2010;Azarpira, 2012). There are two main characteristics in providing learning materials to help students acquire scientific literacy, i.e.…”
Section: Figure 3 Map Location Of Indigenous Knowledge Exploration Imentioning
confidence: 99%
“…Science learning is oriented to the development of caring and responsible attitude towards the social and natural environment (Kabba, 2009;Hewitt et al, 2013). In learning, the material acts as the relationship among separated data sources (Morrison et al, 2007;Adam & Carl, 2010;Azarpira, 2012). There are two main characteristics in providing learning materials to help students acquire scientific literacy, i.e.…”
Section: Figure 3 Map Location Of Indigenous Knowledge Exploration Imentioning
confidence: 99%
“…A study by Azarpira et al in Shiraz showed that inappropriate and poor informing were major weaknesses of Olympiads. 8 Therefore, it is necessary to increase students' awareness about the regulation privileges of the TSO due to joining and using these facilities. So, we could increase the knowledge of students by providing introductory pamphlets about TSO, holding introductory tours in these offices or in the faculties, improving and revising of TSO websites and linking TSO with the Sama System (education management system).…”
Section: Resultsmentioning
confidence: 99%
“…These problems could be partially solved by holding the Scientific Olympiads. 8 Therefore, the universities can discover top students and the strengths and weaknesses of TSOs through these tournaments. The National Medical Science Olympiads are a great and valuable source for studying the effectiveness of facilities on talented students.…”
Section: Introductionmentioning
confidence: 99%
“…The holding of MSSO is one of the effective strategies for this situation, which has been hardly applied in the recent years [7]. Scientific Olympiads are held every year in all over the world in some fields like biology, phasic thinking and protein modeling associated to the Science Ministry [8].…”
Section: Introductionmentioning
confidence: 99%